2018
DOI: 10.3390/agronomy8050076
|View full text |Cite
|
Sign up to set email alerts
|

Concepts and Misconceptions of Humic Substances as the Stable Part of Soil Organic Matter: A Review

Abstract: In the last three decades, the concept of soil humic substances has been questioned in two main directions. Misinterpretations of CP MAS 13 C NMR spectroscopy led to the conclusion that soil organic matter is mainly aliphatic, questioning the theory of polymerization of humic substances from phenolic molecules. Conversely, some critics of humic substances assume that a great proportion of aromatic soil organic carbon originates from fire-affected carbon, often termed as black carbon (BC). However, the determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
78
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(83 citation statements)
references
References 75 publications
3
78
0
2
Order By: Relevance
“…Over the last 3 years, the different suggestions of Lehmann and Kleber (2015) have caused quite a stir among soil scientists (e.g., Piccolo, 2016;Gerke, 2018;Hayes and Swift, 2018;Weber et al, 2018;Olt et al, in press). Defenses of entrenched habits against what is portrayed almost as a heresy have been extremely passionate, and the negative reactions to the proposals made have been very adamant.…”
mentioning
confidence: 99%
“…Over the last 3 years, the different suggestions of Lehmann and Kleber (2015) have caused quite a stir among soil scientists (e.g., Piccolo, 2016;Gerke, 2018;Hayes and Swift, 2018;Weber et al, 2018;Olt et al, in press). Defenses of entrenched habits against what is portrayed almost as a heresy have been extremely passionate, and the negative reactions to the proposals made have been very adamant.…”
mentioning
confidence: 99%
“…Gerke [3] already made some critical comments on the determination of BC in soils. The present paper is a strong extension including some important recent papers (Nakane et al [4]; Zimmermann and Mitra [5]; Wagner et al [6]) and especially Chang et al [7] who showed that the most widely applied method to determine BC-the BPCA method-is not specific for BC.…”
Section: Introductionmentioning
confidence: 99%
“…Another theory states that HS behave in solution as micelles or "pseudo micellar" structures [21]. Also, some authors highlighted the issue that HS might be artifacts forming during the alkaline extraction procedure [22], but this theory has been recently contested [23].Although the existence of these different viewpoints on HS molecular structure, some of their components are critical in the establishment of biotic relationships in the rhizosphere and can interact with plant cell receptors, while triggering plant physiological responses through mechanisms that, so far, are not yet completely elucidated [22].Humic acids (HA) are HS constituents produced via associations of hydrophobic compounds, such as polymethylene chains, fatty acids, phenolics and steroids, which are stabilized by hydrophobic forces at neutral pH [17]. HA isolated from earthworms' coprolites in particular, have been reported to stimulate root growth and plant defense systems against stress [24].…”
mentioning
confidence: 99%
“…Another theory states that HS behave in solution as micelles or "pseudo micellar" structures [21]. Also, some authors highlighted the issue that HS might be artifacts forming during the alkaline extraction procedure [22], but this theory has been recently contested [23].…”
mentioning
confidence: 99%